Implementation Of Electronic Medical Record Information System To Improve Health Services In Remote Areas (HEALTH CARE: JURNAL KESEHATAN, 2025)
In an increasingly digital era, the transformation of data and communication innovation has become key to improving the quality of healthcare services, especially in inaccessible ranges. This ponder points to analyze  the implementation of the Electronic Medical Record (EMR) Wellbeing Data Framework and its affect on the quality of medical services. Based on the data collected, computerrized wellbeing benefit applications in Indonesia show the presence of 63 healthcare services, 82 health information systems, and 51 types of helpdesk that contribute to improving accessibility and efficiency in healthcare delivery. The implementation of EMR is regulated by the Indonesian Medical Council (KKI) regulation number 74 of 2020, which provides a legal framework for the use of technology in healthcare services. This study also examines how EMR can assist in monitoring compliance with treatment protocols, patient waiting times, patient satisfaction levels, and the identification of nutritional issues in the elderly at Siabu Health Center. The evaluation results indicate that the Electronic-Based Government System (SPBE) index varies across provinces, with East Nusa Tenggara Province scoring 2.28 (satisfactory) and North Maluku Territory scoring 1.00 (insufficient). Furthermore, innovations in digital health services enable patients in inaccessible zones to get therapeutic meetings without having to travel long separations, which is crucial for healthcare accessibility. This study is anticipated to supply more profound experiences into the  effectiveness of EMR in improving healthcare quality in remote areas and offer recommendations for the development of policies and infrastructure that support digital transformation in the healthcare sector in Indonesia.